2022
DOI: 10.1029/2022gl098290
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Repartitioning of Stratospheric Inorganic Chlorine After the 2020 Australian Wildfires

Abstract: The inorganic chlorine (Cly) and odd nitrogen (NOy) chemical families influence stratospheric O3. In January 2020 Australian wildfires injected record‐breaking amounts of smoke into the southern stratosphere. Within 1–2 months ground‐based and satellite observations showed Cly and NOy were repartitioned. By May, lower stratospheric HCl columns declined by ∼30% and ClONO2 columns increased by 40%–50%. The Cly perturbations began and ended near the equinoxes, increased poleward, and peaked at the winter solstice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Here we have shown that the effect of wildfire smoke on stratospheric chemistry consists not only of increases in particle surface area (as has been assumed in past literature) 11,32,36 but more importantly in profound impacts on HCl solubility and reactivity. In particular, the 2020 southern hemisphere mid-latitude lower stratospheric composition extremes in HCl, ClONO2, ClO, HOCl are remarkably well reproduced by a model that considers the extremely high solubility of HCl in oxidized wildfire smoke organics at warm stratospheric temperatures (as indicated by historical laboratory solubility data) and subsequent reactions.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Here we have shown that the effect of wildfire smoke on stratospheric chemistry consists not only of increases in particle surface area (as has been assumed in past literature) 11,32,36 but more importantly in profound impacts on HCl solubility and reactivity. In particular, the 2020 southern hemisphere mid-latitude lower stratospheric composition extremes in HCl, ClONO2, ClO, HOCl are remarkably well reproduced by a model that considers the extremely high solubility of HCl in oxidized wildfire smoke organics at warm stratospheric temperatures (as indicated by historical laboratory solubility data) and subsequent reactions.…”
Section: Discussionsupporting
confidence: 64%
“…7. compared to the effects of interannual dynamical variability at mid-latitudes, and there is evidence for some dynamically-driven decreases in ozone in 2020 1,36 .…”
Section: Most Of the Chlorine Released From Chlorofluorocarbons Resid...mentioning
confidence: 99%
“…We focus this analysis on the SH midlatitudes, 38°S-54°S EqL, and the SH tropics, 6°S-22°S EqL. The former allows comparison of the volcano-induced perturbations in chlorine and nitrogen partitioning with those engendered by the Australian New Year's (ANY) fires in late 2019/early 2020 (Santee et al, 2022;Solomon et al, 2022Solomon et al, , 2023Strahan et al, 2022) and is also characterized by somewhat better ACE-FTS data coverage; the latter experiences the largest HT-HH impacts on stratospheric composition but suffers from poor ACE-FTS sampling. We also briefly examine the intermediate region of the SH subtropics, 22°S-38°S EqL.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors could, and are, delaying ozone recovery. These include large wildfires, which will become more frequent and intense in a changing climate (Solomon et al., 2022, 2023; Strahan et al., 2022), major volcanic eruptions (Lu et al., 2023; Tie & Brasseur, 1995), emissions of currently unregulated ozone‐depleting substances (Fang et al., 2019; Ravishankara et al., 2009), and illegal emissions of controlled ozone‐depleting substances (Dameris et al., 2019; Montzka et al., 2018). While the Montreal Protocol has been enormously successful in phasing out halogen‐containing source gases, the ozone layer is far from a solved problem.…”
Section: Resultsmentioning
confidence: 99%